2003
DOI: 10.1080/0020723032000069204
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of dissolved Mn, Zn, Ni and Cu During the mixing of tadjan river water with caspian sea water

Abstract: This is the first study of flocculation of dissolved Zn, Cu, Ni and Mn during the mixing of Tadjan River water with the largest lake in the world (the Caspian Sea). Flocculation of Dissolved metals was investigated on a series of mixtures with salinities ranging from 0.16 to 9.5 ppt. The flocculation rates (Zn (96%) > Mn(58%) > Cu(42%) > Ni(7%)) are indicative of the non-conservative behavior of Zn, Mn and Cu and the conservative behavior of Ni during estuarine mixing. Statistical analysis indicates that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The concentration of studied metals in Minab River water during estuarine mixing has been compared with the concentration of elements in flocculants of five rivers flowing into the Caspian Sea in North of Iran (Table 2). As can be seen in Table 2, except for Zn and Pb other studied elements in Minab River water flocculate at higher rates in comparison with the river flowing into the Caspian Sea (Karbassi and Nadjafpour, 1996;Saeedi et al, 2003;Karbassi et al, 2007;Karbassi et al, 2008a,b) and this might be due to higher initial metal contents in Minab River water than the northern river of Iran (Biati et al, 2010 b). The lowest flocculation rate in Minab river is associated with Pb (38 %) and in Tadjan, Talar, Babolrud and Haraz (Rivers flowing into the Caspian Sea) Ni flocculates in the lowest rate (7.1 %, 18.8 %, 12.2 % and 11.3 %, respectively).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The concentration of studied metals in Minab River water during estuarine mixing has been compared with the concentration of elements in flocculants of five rivers flowing into the Caspian Sea in North of Iran (Table 2). As can be seen in Table 2, except for Zn and Pb other studied elements in Minab River water flocculate at higher rates in comparison with the river flowing into the Caspian Sea (Karbassi and Nadjafpour, 1996;Saeedi et al, 2003;Karbassi et al, 2007;Karbassi et al, 2008a,b) and this might be due to higher initial metal contents in Minab River water than the northern river of Iran (Biati et al, 2010 b). The lowest flocculation rate in Minab river is associated with Pb (38 %) and in Tadjan, Talar, Babolrud and Haraz (Rivers flowing into the Caspian Sea) Ni flocculates in the lowest rate (7.1 %, 18.8 %, 12.2 % and 11.3 %, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Statistical analysis reveals that the flocculation of dissolved metals in Tadjan river which is governed by pH has an inverse relationship with TOC, EC and salinity. This suggests that increasing salinity, TOC and EC leads to a decrease of pH and elemental flocculation (Saeedi et al, 2003). Karbassi and Nadjafpour (1996) concluded that in Shirud Estuary, the main governing factor of metal flocculation (Pb and Zn) is salinity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to their findings, exobiological factors such as temperature, ion number, sediment type, and size of sediment particles, pH, and the simultaneous existence of several heavy metals affect the amount of heavy metals adsorption on the sediments. Some studies on the heavy metals pollution and their behavior in Iranian rivers have been conducted recently (Saeedi et al 2003(Saeedi et al , 2004Saeedi and Karbassi 2008;Karbassi and Nadjafpour 1996;Karbassi et al 2007Karbassi et al , 2008, but the adsorption process of metals onto the sediments is rarely studied.…”
Section: Introductionmentioning
confidence: 99%